Alopecia Management An Update - Montero-Vilchez, Trinidad; Arias-Santiago, Salvador (IntechOpen, 2023)
Discover the latest advancements in alopecia management with Alopecia Management - An Update. This comprehensive edited volume brings together leading experts in the field to provide a timely and informative exploration of strategies for managing alopecia. Covering a wide range of topics, this book offers valuable insights into understanding the different types and causes of alopecia, addressing its emotional and psychological impact, practical hair care tips, and emerging therapies. With its cohesive and logically arranged chapters, Alopecia Management - An Update is an essential resource for individuals affected by alopecia, caregivers, and healthcare professionals. Benefit from the expertise of renowned contributors who share their knowledge and experiences in this comprehensive volume. Explore the latest advancements in alopecia management, make informed decisions, and enhance your understanding of this condition.